Pengaruh Promosi Instagram dan Marketplace Shopee untuk Meningkatkan Kesadaran Merek dengan Menggunakan Sensitivitas Harga sebagai Variabel Intervening (Survei Konsumen Keramik Mulia di Toko Aneka Keramik Bekasi) - Christian, Nico; Renwarin, Joseph Martinio Jocrien; Rianto, Muhammad Richo; Thamrin, Djuni; Siahaan, Matdio; Sakti, Pricilia Johani (Al-DYAS, 2025)
Indonesia's ceramics industry has undergone significant changes in the online business world over the past five years. Many local ceramic companies have developed innovative products and designs to meet the changing tastes of consumers. Ceramic products are now considered important aesthetic elements in the construction of indoor and outdoor areas, and are no longer merely functional everyday items. This study aims to examine the impact of promotional activities on Instagram and the Shopee marketplace, the role of price sensitivity as an intervening variable in the relationship between Instagram promotions and brand awareness of Aneka Keramik stores, and the role of price sensitivity as an intervening variable in the relationship between Shopee marketplace promotions and brand awareness of Aneka Keramik stores. This study employs a quantitative approach, utilizing a questionnaire to collect data through surveys of consumers who purchase Mullia ceramic products from Aneka Keramik stores via the Instagram and Shopee marketplaces.The study's population consists of consumers who have purchased Mullia ceramic products from Toko Aneka Keramik through Instagram and the Shopee marketplace.The study's sampling method is non-probability, employing a purposive sampling approach. The Lameshow formula was used to determine a sample size of 100 people.The results of the study indicate that Instagram promotion has a significant effect on price sensitivity (p < 0.05). Shopee promotion has a significant effect on brand awareness (p = 0.022). Instagram promotion has a significant effect on brand awareness (p = 0.018). The Shopee promotion has no significant impact on brand awareness (p = 0.114), while the Instagram promotion has a significant impact (p = 0.004). The Shopee promotion has no significant impact on brand awareness (p = 0.155). Price sensitivity has a significant impact on brand awareness (p = 0.018).